Heterologous expression of xylanase gene from bacillus sp. in e. coli bl21 (DE3) - Arutchelvan, Rajamanikam (Universiti Malaysia Sarawak, UNIMAS, 2010)
Xylanase gene of 642 bp with molecular weight 23kDa which was isolated from indigenous Bacillus sp. The isolated xylanase gene from indigenous Bacillus sp. was cloned into pET expression vector to obtain a high level expression of this recombinant family 11 xylanase in expression host E.coli BL21 (DE3). This attempt to clone the gene was initiated with the extraction of xylanase gene previously isolated from pGEM®-T easy cloning vector. The cloning vector was digested with restriction endonuclease and the xylanase insert was cloned into pET41(a) and transformed into E.coli BL21(DE3) via heat shock transformation. The expression was attempted to be observed through formation of halos in congo red staining method. Qualitative xylanase screening showed no detectable xylanase activity. This was predicted to be due to reasons like improper framing (frameshift) of cloned xylanase gene to LacZ promoter or incapability of E.coli BL21(DE3) to grow optimally in M9 minimal media with corn cob xylan source. It is highly recommended to get the full sequence of recombinant pET41(a)-Xyn to confirm the position of ligation of xylanase gene. The minimal media should also be altered in salt composition for optimized growth of E.coli BL21 (DE3).